Analisis Penempatan Recloser Untuk Mendapatkan Indeks Keandalan Terbaik Menggunakan Metode Ant Colony Optimization (ACO) - Dwidana, Atikah Zahrah; Sukma, Dian Yayan; Feranita, Feranita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The distribution system is an important part of the electrical energy distribution activities as directly connected to the customers. Therefore, the distribution system is always required to have good reliability. One of solution to increase reliability is using recloser in the medium voltage feeder.Optimal placement of recloser will be able to maximize reliability. In this researched, the author used a Ant Colony Optimizization method in determining the optimal position of recloser. Objective function is combining SAIFI and SAIDI. SAIFI and SAIDI are calculated using section technique method. Simulation calculations using MATLAB (Matrix Laboratory) programming. Program testing was carried out on the Gurami Feeder network at PT. PLN (Persero) ULP West City Pekanbaru Area which distributes electrical energy sourced from the Garuda Sakti Substation. Gurami feeder is a radial distribution network. Based on the application of the ACO method, the best position for placing the addition of a recloser on the main feeder before the distribution transformer is KB-0508 (100kVA). The addition of the recloser with the best position resulted in a reduction in the SAIDI value from the initial value of 16.647 hours/year to 14.040 hours/year and the SAIFI value from the initial value of 18.907 times/year to 15,928 times/year. Keywords: reliability, ant colony optimizazition, section technique, recloser.